Relevansi Program Makan Bergizi Gratis (MBG) di Indonesia dengan Prinsip Maqashid Syariah: Hifz al-Nafs - Ahmad Muhyidin; Muhammad Syarofi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the relevance of Indonesia’s Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) to the framework of Maqashid Shariah, with a particular focus on the principle of Hifz al-Nafs (protection of life). As a strategic national policy regulated through the Decree of the Head of the National Nutrition Agency No. 63 of 2025, MBG is designed to address malnutrition and improve human resource quality. This research seeks to examine whether the program substantively aligns with Islamic ethical objectives centered on human welfare and life preservation. This study employs a qualitative normative approach using a maqashid-based policy analysis. Data were collected through a systematic review of policy documents, including technical guidelines of MBG, official government reports, and relevant academic literature on Maqashid Shariah and public health policy. The analytical framework is grounded in classical and contemporary Maqashid Shariah theory, emphasizing Hifz al-Nafs as a primary objective (daruriyyat). Data were analyzed inductively through thematic coding to identify policy components that reflect life protection and health security. The findings indicate that MBG demonstrates strong alignment with Hifz al-Nafs through strict hygiene standards, targeted nutrition for vulnerable groups, quality control mechanisms, and balanced nutrient provision based on recommended dietary allowances. The program also indirectly supports Hifz al-‘Aql and Hifz al-Nasl by enhancing cognitive development and safeguarding future generations. However, challenges remain regarding implementation consistency and regional capacity. The study concludes that MBG is substantively relevant to Maqashid Shariah, particularly Hifz al-Nafs, positioning the program as both a public health intervention and an ethical instrument for societal welfare. Integrating Maqashid Shariah into policy evaluation provides a normative foundation for strengthening equitable and sustainable nutrition policies.